2012
DOI: 10.4414/smw.2012.13689
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bispectral index monitoring on extubation time and analgesic consumption in abdominal surgery: a randomised clinical trial

Abstract: Guiding anaesthesia according to BIS level will result in significantly faster recovery after anaesthesia. The investigation was registered on ClinicalTrials.gov (NCT01470898).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 7 publications
2
7
0
1
Order By: Relevance
“… 5 , 13 In young patients with ASA physical status I–II, the BIS value can be restored to the preanaesthesia level within 5 min after extubation. 5 , 6 Therefore, this study was designed to record the BIS values and Steward recovery scores in elderly patients for up to 15 min after extubation. The BIS value during surgery can have an impact on the quality of the recovery in elderly patients under general anaesthesia; and fluctuations in BIS values might be obvious at the point of the initial skin incision, when cutting the gallbladder, suturing the peritoneum, and during final skin closure in patients undergoing transabdominal cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 5 , 13 In young patients with ASA physical status I–II, the BIS value can be restored to the preanaesthesia level within 5 min after extubation. 5 , 6 Therefore, this study was designed to record the BIS values and Steward recovery scores in elderly patients for up to 15 min after extubation. The BIS value during surgery can have an impact on the quality of the recovery in elderly patients under general anaesthesia; and fluctuations in BIS values might be obvious at the point of the initial skin incision, when cutting the gallbladder, suturing the peritoneum, and during final skin closure in patients undergoing transabdominal cholecystectomy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with the T 0 preinduction BIS data, the BIS values at T 9 and T 10 and the corresponding Steward recovery scores between the two groups showed no significant difference, which was consistent with the results of a previous study. 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…performed similar study with sevoflurane and observed a significantly shorter extubation time (17.5 min vs. 75 min, P < 0.001) in the BIS-guided group as compared to ETAG group. [ 11 ] On the contrary, Villafranca et al . performed a study in fast-track cardiac surgery using sevoflurane or desflurane.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10] Son yıllarda giderek kullanımı artan bispektral indeks (BİS) monitörizasyonu ile hastaya uygulanacak anestezik ajan miktarının titre edilerek azaltılabileceği, daha hızlı derlenmenin sağlanabileceği, postoperatif yoğun bakımda kalış süresinin kısalabileceği bildirilmektedir. 7,[10][11][12][13][14][15] Bu çalışmada, majör abdominal cerrahi operasyonlarında üç farklı anestezi uygulamasının intraoperatif anestezik ajan gereksinimi, postoperatif analjezi kalitesi ve cerrahiye endokrin-metabolik stres yanıt üzerine erken ve geç dönem etkilerinin karşılaştırılması amaçlanmıştır.…”
unclassified